Will wealth inequality decrease happiness?—Empirical evidence from China - Wang, Jingtao (Frontiers in Psychology, 2024)
Introduction This article delves into the broad social and economic impacts of wealth inequality, specifically focusing on its effects on happiness, as analyzed using micro survey data from the China Family Panel Studies (CFPS). Methods This article employs the panel OLS regression method with time and province fixed effects for the main result and heterogeneity analysis, then uses the mediating effect and moderating effect test for the mechanisms. Results and discussion The article presents several key findings: 1. Impact of Wealth Inequality on Happiness. The study confirms that wealth inequality significantly reduces happiness, a conclusion reinforced by a range of consistency tests and endogeneity checks. 2. Heterogeneity Analysis. Three areas of heterogeneity are examined: Hukou status, education level, and family members’ average income. The results indicate that the happiness of families with a family head holding an urban Hukou, higher education, or a higher per-member income level is less affected by wealth inequality. 3. Mechanisms Affecting Happiness. At the micro-level, the article identifies two mediating pathways—health and marital status—through which wealth inequality negatively influences happiness. At the macro-level, it is found that social security expenditure and economic development can moderate these effects and enhance subjective happiness under the same conditions of wealth inequality. The contributions of this study are specific as: 1. This study addresses some of the existing gaps in the research regarding the relationship between wealth inequality and happiness. 2. The article utilizes relative deprivation as a measure of wealth inequality, considered a more apt metric for studying happiness compared to absolute inequality. 3. This research offers insights into the mechanisms behind the observed effects, considering both micro-level (individual and family) and macro-level (societal and economic) factors.